2003
DOI: 10.1108/03090560310495474
|View full text |Cite
|
Sign up to set email alerts
|

Market orientation in Nordic banks: does nationality matter?

Abstract: Neither market orientation nor the possible link to performance is easily achieved and in various countries companies may organize differently to cope with the information-processing and customer-responding challenges. Nationwide surveys in banks in Denmark, Finland, Norway, and Sweden indicate that a path to performance involves innovations such as "supported empowerment" though there are differences in the antecedents of market orientation. Thus the most distinct Scandinavian ways to improvements may be foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…For 8 of the last 11 years in that data, new entrants dominated the award; in fact, in the last 5 years of that study, one winner was a virtual bank and another was a subsidiary of a retail grocery chain. It was suggested that observations could carry practical implications; Nielsen, HØst, Jaensson, Kock and Selnes (2003), in a more general study of Nordic banking, ascertained that customer-focused banks tended to be associated with positive market-performance, whereas complacency on the other hand was associated with lower performance-an observation that appears consistent with other earlier studies that customer satisfaction tended to affect performance either directly or indirectly (Chuah & Devlin, 2011;Caruana, 2002; Athanassopoulos, Gounaris, & Stathakopoulos, 2001;Devlin, 2001;Lassar, Manolis, & Winsor, 2000;Angur, Nataraajan, & Jahera, 1999;Yavas, Bilgin, & Shemwell, 1997;Lewis, 1993).…”
Section: Banks and Banking In Swedenmentioning
confidence: 51%
“…For 8 of the last 11 years in that data, new entrants dominated the award; in fact, in the last 5 years of that study, one winner was a virtual bank and another was a subsidiary of a retail grocery chain. It was suggested that observations could carry practical implications; Nielsen, HØst, Jaensson, Kock and Selnes (2003), in a more general study of Nordic banking, ascertained that customer-focused banks tended to be associated with positive market-performance, whereas complacency on the other hand was associated with lower performance-an observation that appears consistent with other earlier studies that customer satisfaction tended to affect performance either directly or indirectly (Chuah & Devlin, 2011;Caruana, 2002; Athanassopoulos, Gounaris, & Stathakopoulos, 2001;Devlin, 2001;Lassar, Manolis, & Winsor, 2000;Angur, Nataraajan, & Jahera, 1999;Yavas, Bilgin, & Shemwell, 1997;Lewis, 1993).…”
Section: Banks and Banking In Swedenmentioning
confidence: 51%
“…18,50,53,70,71 However, the degree to which employees in different parts of the world perceive market orientation differs.…”
Section: Mean Rating Of Dimensionsmentioning
confidence: 96%
“…50,52,64 Each of the items in all the dimensions utilized the 5-point Likert-type scale that ranged from 1 = strongly disagree to 5 = strongly agree. 13,18,20,50,52 Section D of the questionnaire was mainly meant to solicit personal information from respondents, such as job title, age, gender, number of years working with the bank, educational background and rank. The demographic information was required for the purpose of classifi cation and examination of the relationship between employee status and their perception of market orientation.…”
Section: Measurement Instrumentmentioning
confidence: 99%
See 1 more Smart Citation
“…This study will review the literature which is similar to those demographic factors that is company's size. According [29] to understand the mechanism of market orientation and its development, the size of organizations has to be taken into account. According to a study by [30], they stated that the relationship between market orientation and performance changes with the changes in the size of company.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%